Evaluation of soil carbon stocks in response to management changes in sugarcane production - Zani, Caio Fernandes (2015)
Brazilian commodities, such as ethanol, are looking for sustainable production to suit the international market demands. An important parameter for assessing sustainability is the carbon (C) footprint calculation of the product. Thus, studies of the variations in soil C stocks on the ethanol production are essential. Studies in relation to land use change are already been developed; however information about parameters of management changes on the sugarcane production is needed. The aim of this research was to evaluate the soil C stock in response to two main management changes in sugarcane production: i) no vinasse to vinasse application (NV-V), ii) burned to unburned harvesting system (B-UB). We also evaluated soil C stock changes in a chronosequence irrigation practices (native vegetation (NV), sugarcane irrigated 4 years (I4) and 6 years (I6), a new management in semi-arid and drought regions in Brazil which also aims high yields. Modelling approaches in order to assess long-term effects were also analysed. The NV-V transition showed higher soil C stock for V regime for topsoil layers 0-40 cm depth mainly due to the addition of organic compounds to the soil. Vinasse can also enhance biomass production and crop yield. The B-UB transition showed higher soil C stock in the UB regime from 20 to 60 cm depth due to higher organic matter accumulation from the maintenance of the straw to the field. The cumulative soil C stock for 1 metre depth had an increase of 1.1 and 0.75 Mg C ha-1 y-1 in the NV-V and B-UB transitions, respectively. From modelling was observed that V and UB sites had an increase of soil C stock by 2150, being a difference of 2.8 and 23 Mg ha-1 in the equilibrium state between NV-V and B-UB regimes, respectively. In the irrigation practices, the I4 showed higher soil C stock than NV in the 20 to 40 cm; while I6 was lower than NV in the 50 to 100 cm depth. Simulated long-term analyses showed increase of topsoil C stock of 12 and 13 Mg ha-1 for I6 and I4 area, respectively, compared to NV on 2100. The results in this study are pioneers in relation to soil C stock studies in the management transitions and irrigation practices. This information may be used as a basis for public policies decision which dealing of the land use and global warming